Exploiting ovine immunology to improve the relevance of biomedical models. Issue 1 (July 2015) - Entrican, Gary; Wattegedera, Sean R.; Griffiths, David J.
Highlights Sheep make a valuable contribution to immunology research. Lessons to be learned from studying infections in the natural host. Factors to consider when selecting biomedical models.